Comparative activity of a polyhexanide–betaine solution against biofilms produced by multidrug-resistant bacteria belonging to high-risk clones. Issue 1 (September 2019) - Machuca, J.; Lopez-Rojas, R.; Fernandez-Cuenca, F.; Pascual, Á.
Summary: The aim of this study was to investigate the effect of polyhexanide (polyhexamethylene biguanide)–betaine (PHMB-B) compared with 2% chlorhexidine against biofilms of high-risk and/or multidrug-resistant bacterial clones. The minimum inhibitory concentrations of both biocides were determined by microdilution. The effect of PHMB-B and chlorhexidine on biofilm was evaluated by spectrophotometry and cell viability assays. At commercial concentrations, PHMB-B reduced 24 h, 48 h and 1-week biofilms of all pathogens tested. PHMB-B was more active than 2% chlorhexidine against Gram-negative bacterial 24 h and 48 h biofilms and Gram-positive bacterial 7-day biofilms. In summary, the activity of PHMB-B was superior to that of 2% chlorhexidine in those biofilms.